2022
DOI: 10.3390/ijms23179524
|View full text |Cite
|
Sign up to set email alerts
|

Mutant WDR45 Leads to Altered Ferritinophagy and Ferroptosis in β-Propeller Protein-Associated Neurodegeneration

Abstract: Beta-propeller protein-associated neurodegeneration (BPAN) is a subtype of neurodegeneration with brain iron accumulation (NBIA) caused by loss-of-function variants in WDR45. The underlying mechanism of iron accumulation in WDR45 deficiency remains elusive. We established a primary skin fibroblast culture of a new BPAN patient with a missense variant p.(Asn61Lys) in WDR45 (NM_007075.3: c.183C>A). The female patient has generalized dystonia, anarthria, parkinsonism, spasticity, stereotypies, and a distinctiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…A widely acknowledged hypothesis regarding the 'atypical form' of parkinsonism, an emerging important feature of these disorders, with its rapid progression and cognitive decline is that massive protein and organellar accumulation may lead to excessive neuronal waste and degeneration 63 . Previous reports identified autophagopathies such as WDR45 defects as the cause of both childhood NDD 46 and early adulthood parkinsonism 64 , suggesting substantial clinico-pathological overlap reflective of the molecular interactions between EPG5 and WDR45 in the autophagosome-lysosome fusion machinery (Figure 6). The autophagosome-lysosome fusion machinery is rapidly emerging as a hotspot for neurological disease, with pathogenic variants also in SNAP29, RAB7A, and HOPS complex components implicated in a wide range of neurological diseases [65][66][67][68] , highlighting a promising target for future investigations.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 90%
“…A widely acknowledged hypothesis regarding the 'atypical form' of parkinsonism, an emerging important feature of these disorders, with its rapid progression and cognitive decline is that massive protein and organellar accumulation may lead to excessive neuronal waste and degeneration 63 . Previous reports identified autophagopathies such as WDR45 defects as the cause of both childhood NDD 46 and early adulthood parkinsonism 64 , suggesting substantial clinico-pathological overlap reflective of the molecular interactions between EPG5 and WDR45 in the autophagosome-lysosome fusion machinery (Figure 6). The autophagosome-lysosome fusion machinery is rapidly emerging as a hotspot for neurological disease, with pathogenic variants also in SNAP29, RAB7A, and HOPS complex components implicated in a wide range of neurological diseases [65][66][67][68] , highlighting a promising target for future investigations.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 90%
“…While we were working on this project, other studies suggested that WDR45 depletion causes ferroptosis [29][30][31] . However, these reports, which were cell-culture based, suggested that the ferroptosis was due to defective autophagy-dependent mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The mitochondrial network was investigated as previously described [ 21 , 22 ]. Cells were either stained under basal conditions or after treatment with paraquat (2 mM) for 5 h. Subsequently, the mitochondrial network in the fibroblasts was stained with an anti-GRP75 antibody (1:1000, Abcam, Cambridge, MA, USA) in combination with the Zenon immunolabelling kit (Invitrogen, Carlsbad, CA, USA) according to the manufacturer’s protocol.…”
Section: Methodsmentioning
confidence: 99%